Programa nacional de reorientação da formação profissional em saúde pró-saúde como política norteadora do processo de reformulação curricular do curso de enfermagem da Universidade federal do acre - Aguiar, Katiuscia Larsen de Abreu [UNIFESP] (2013)
Training of human resources in health has been constituted national and international rich field of research. In Brazil, several programs aiming to improve workforce in health arose from the establishment of the Unified Health System - SUS and, among them there are the National Reorientation of Vocational Training in Health - Pro-Saúde. Similarly, an important movement between Health and Education took place with the advent of the National Curriculum Guidelines - DCN, enhancing current education for health professionals. The Universidade Federal do Acre, campus Rio Branco - UFAC/RB was established in 1974 with the Undergraduate Nursing course in order to meet the health care needs of the region. The importance of Political Pedagogical Project - PPP of the course was emphasized since it had only five revisions in thirty-eight years, being the privileged space for these interactions. General Objective: This study aimed to recognize the need to change the process of nursing education based on the National Reorientation of Vocational Training in Health – Pró-Saúde, as well as in accordance with the National Curriculum Guidelines- DCN for the Undergraduate Nursing Program at the UFAC/RB. Specific objectives: Identify the Pró-Saúde potential as an inducer of the teaching-service integration, improving the nursing course of the Universidade Federal do Acre / Rio Branco - UFAC/RB; to characterize the transformation process of the Nursing Course in relation to teaching/service integration; to investigate the mobilization and influence triggered by the Pró-Saúde in the Curriculum Committee of the Nursing Course ; apprehend managers´ perceptions about the process of curricular reorientation of the Nursing Course at the Universidade Federal do Acre / Rio Branco - UFAC/RB. Methodology: Using qualitative and quantitative approach with the following instruments: case study, documentary analysis on Pedagogical Political Projects - PPP of the Nursing Course of the UFAC/RB, the DCN and the Pró-Saúde program. A Likert-type attitudinal scale was used with four dimensions with 17 assertions in its contents and statistically validated by linear correlation, test reliability and homogeneity. Results: good perception regarding mobilization and influence triggered by Pro-Saúde in the curriculum committee of the Undergraduate Nursing Course UFAC/RB; the need for immediate changes and improvement related to the identification of Pró- Saúde potential as an inducer of improvement of the teaching-service integration in the Course of Nursing UFAC-RB; characterization of the transforming process of the Nursing Course UFAC-RB in relation to teaching-service integration and apprehension of managers' perceptions about the process of curricular reorientation of Nursing Course at UFAC-RB. Conclusion: Perception of an harmony between all actors in the Course of Nursing UFAC/RB based on the National Reorientation of Vocational Training in Health - Pró-Saúde, National Curriculum Guidelines - DCN Pedagogical Political Projects - PPP in relation to Human Resources training in Nursing; need of adjustments in the academic process operationalization; educational qualification of the academic staff, to improve practice, search for greater integration between the activities of teaching, research and extension, offering a curricular space for discussion of issues relating to ethics, citizenship, among others.